Understanding the Causes, Consequences, and Effective Interventions for Illiteracy in Indonesia: A Systematic Literature Review - Zakiah, Andi Sitti; Arismunandar, Arismunandar; Aswi, Aswi (Indonesian Educational Administration and Leadership Journal (IDEAL), 2026)
Illiteracy remains a significant educational challenge in Indonesia despite continuous improvements in educational access and national literacy initiatives. This study aims to systematically synthesize recent empirical evidence on the determinants of illiteracy, its multidimensional impacts, intervention strategies, and the effectiveness of literacy programs implemented in Indonesia. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was retrieved using the Elicit academic search platform, with studies published between 2022 and 2026. After the screening and eligibility assessment, 28 studies were included in the qualitative synthesis. The findings indicate that illiteracy is influenced by interconnected individual, family, school, community, and policy-related factors. Beyond educational consequences, illiteracy negatively affects employment opportunities, social participation, health literacy, and human resource development. The reviewed studies identified five major categories of literacy interventions: technology-based, culture-based, instruction-based, policy/program-based, and materials-based strategies. Overall, the available evidence suggests that interventions integrating interactive learning, culturally relevant content, student-centered pedagogy, and collaboration among schools, families, communities, and government institutions tend to be more effective in improving literacy outcomes. However, the predominance of short-term intervention studies indicates the need for more longitudinal and large-scale research to strengthen the evidence base. This review suggests that sustainable literacy improvement is more likely to be achieved through comprehensive, context-sensitive, and multi-stakeholder approaches that address the diverse educational contexts across Indonesia.